Penggunaan Masker Kain dalam Pencegahan Penularan COVID-19 - Rudi Saputra (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2020)
Introduction: COVID-19 (Coronavirus Disease 2019) is a new disease due to SARS-CoV-2 (Severe Acute Respiratory Syndrome-Coronavirus-2) which can be transmitted through droplets. One effort to prevent transmission of COVID-19 is to use a mask. Medical masks are effective in preventing transmission of COVID-19, but their numbers are very limited and are very much needed by medical personnel when treating COVID-19 patients. Therefore, to prevent the spread of COVID-19 more broadly, alternative medical masks are needed, namely by using cloth masks which have not been discussed much about the purpose of their use to the public. Discussion: SARS-CoV-2 is a cause of COVID-19 and infects the respiratory tract, especially in the lungs (pulmo) through the ACE2 receptor (Angiotensin-Converting Enzyme 2). SARS-CoV-2 has a diameter of around 120 nm. Cloth masks as an alternative to the scarcity of medical masks are recommended for public use. The recommended cloth masks are made of cotton or a cloth towel. A cloth mask is able to hold large droplets (> 5 ?m), but not small droplets. Conclusion: Cloth masks can be used by the community in an effort to minimize transmission of COVID-19 by holding large droplets, but it is not effective in preventing transmission of COVID-19 because it can still be passed by SARS-CoV-2. Suggestion: Cloth masks can be optimized using nanoparticles to resist SARS-CoV-2.